STRATEGI PENGEMBANGAN PEMBELAJARAN PAI DALAM MENINGKATKAN PRESTASI SISWA DI SMPN 3 PETERONGAN - Sirojudin, Didin; Issyiami, Nur Khaqiqi (Universitas KH. A. Wahab Hasbullah, 2021)
Learning can be said to be successful if the objectives have been achieved. To achieve this goal, various strategies and methods are needed that are relevant and in accordance with the times. This research was conducted to find out how the achievements of SMPN 3 Peterongan students both in the religious and non-religious fields as well as in the academic and non-academic fields because it is known that SMPN 3 Peterongan is one of the schools that has various kinds of achievements in all fields. In addition, it is also to find out how the process of the strategies and methods used and how to solve the existing obstacles. This study uses a qualitative approach with a descriptive method which assigns the researcher as the main tool to search for all data from various available sources. One of them is by way of researchers going to the research site and conducting interviews with informants, then the results of the interviews are reported descriptively and narratively. The results of this study are SMPN 3 Peterongan can achieve various achievements, especially in the field of religion, one of which is by integrating two curricula at once without any differences or ruling out one another. The curriculum is an official curriculum and a religious curriculum that always goes hand in hand. By merging the two curricula, students will not only excel in the religious field but also excel in the non-religious field. And all kinds of obstacles that occur in the process of developing this learning will also be resolved properly by means of deliberation to reach consensus in order to achieve our common goals.